Correlation of Platelet Count and Acute ST-Elevation in Myocardial Infarction - Paul, GK; Sen, B; Bari, MA; Rahman, Z; Jamal, F; Bari, MS; Sazidur, SR (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):469-73 The abstract of this article is available on the PubMed website